2018
DOI: 10.3390/ijerph15030442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Driving Factors of Construction Industrialization Development in China

Abstract: Construction industrialization (CI) has been adopted worldwide because of its potential benefits. However, current research shows the incentives for adopting CI may differ in different regions. While the promotion of CI in China is still at the initial stage, a systematical analysis of the driving factors would help decision makers get a comprehensive understanding of CI development and select proper strategies to promote CI. This research combines qualitative and quantitative methods to explore the constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These various results can be due to the several reasons such as construction methods, the risk analysis model entailing meta network analysis, grounded theory, Analytic Network Process (ANP), the linear weighted sum method and structured selfintersection matrix that might have been effective in these conclusions. Some other related justifications and discussions can be found in Xiahou et al (2018) and Lu et al (2018).…”
Section: Comparing Average Of Rcn For Each Classmentioning
confidence: 97%
“…These various results can be due to the several reasons such as construction methods, the risk analysis model entailing meta network analysis, grounded theory, Analytic Network Process (ANP), the linear weighted sum method and structured selfintersection matrix that might have been effective in these conclusions. Some other related justifications and discussions can be found in Xiahou et al (2018) and Lu et al (2018).…”
Section: Comparing Average Of Rcn For Each Classmentioning
confidence: 97%
“…For example, Jin et al [44] reviewed and analysed journal articles on off-site construction from 2008 to 2018 through bibliometrics retrieval and scientometric analysis, summarised the main research topics and research gaps for off-site construction and proposed a framework for future research. Jin et al [93] reviewed and analysed the research on the environmental performance of off-site construction facilities by using the life cycle method and bibliometric analysis. It is generally believed that off-site construction (OSC) methods, such as prefabrication and modular construction, have become promising construction methods to solve traditional on-site construction challenges, including productivity, logistics, pollution, safety, waste, quality, cost and subjectivity to the environment and weather [94].…”
Section: Modular Construction and Off-site Constructionmentioning
confidence: 99%
“…Researchers assessed the influence of these perceived characteristics on the adoption of innovation in the housing sector. They found that innovations should possess some form of relative advantage over alternatives (Table VI) (McCoy et al, 2012;Mlecnik et al, 2010;Xiahou et al, 2018). In particular when homeowners are involved in the adoption decision-making process, the relative advantage should encompass immediate benefits such as comfort improvement or the replacement of particular building components because of their poor physical condition (Achtnicht and Madlener, 2014;Baumhof et al, 2018;Nair et al, 2010b;Roders and Straub, 2015;Swan et al, 2013b).…”
Section: Mechanisms Affecting the Adoption Of Innovation In Housingmentioning
confidence: 99%
“…lack of interoperability and fit in existing supplier relations), it diminishes the propensity to adopt the innovation (Gan et al, 2015;Mlecnik et al, 2010). In addition, evidence has been found that innovations could benefit from result demonstrability and trialability (Mueller and Berker, 2013;Xiahou et al, 2018;McCoy et al, 2012;Mlecnik et al, 2010). In contrast, perceived risk concerning the impact of negative consequences for applying the innovation hinders the adoption of innovation (McCoy et al, 2012;Mlecnik et al, 2010).…”
Section: Mechanisms Affecting the Adoption Of Innovation In Housingmentioning
confidence: 99%